2001
DOI: 10.1096/fj.00-0300com
|View full text |Cite
|
Sign up to set email alerts
|

Altered mitochondrial function and overgeneration of reactive oxygen species precede the induction of apoptosis by 1‐O‐octadecyl‐2‐methyl‐rαc‐grycero‐3‐phosphocholine in p53‐defective hepatocytes

Abstract: The mechanism of induction of apoptosis by the novel anti-cancer drug 1-O-octadecyl-2-methyl-rac-glycero-3-phosphocholine (ET-18-OCH3) was investigated in p53-defective SV40 immortalized rat hepatocytes (CWSV1). Exposure to 12 microM ET-18-OCH3 for 36 h induced apoptosis as determined using classical morphological features and agarose gel electrophoresis of genomic DNA. Increased levels of reactive oxygen species (ROS) were detected spectrophotometrically using a nitroblue tetrazolium (NBT) assay in cells trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
96
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 43 publications
(49 reference statements)
2
96
0
1
Order By: Relevance
“…We have used in this work rotenone, the inhibitor of the respiratory chain Complex I, to modulate mitochondrial basal ROS generation. This approach, which has been pursued in many laboratories, has produced conflicting results reporting that rotenone could elevate cellular ROS generation in some cases [16,30,31], but reduce ROS production in others [12,15,[32][33][34]. Data have recently been produced showing that ROS generated during the oxidation of NAD-dependent substrates are greatly enhanced by rotenone and exclusively released into the mitochondrial matrix [15,16], where they are dissipated by the matrix antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…We have used in this work rotenone, the inhibitor of the respiratory chain Complex I, to modulate mitochondrial basal ROS generation. This approach, which has been pursued in many laboratories, has produced conflicting results reporting that rotenone could elevate cellular ROS generation in some cases [16,30,31], but reduce ROS production in others [12,15,[32][33][34]. Data have recently been produced showing that ROS generated during the oxidation of NAD-dependent substrates are greatly enhanced by rotenone and exclusively released into the mitochondrial matrix [15,16], where they are dissipated by the matrix antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of mitochondrial respiratory chain complex I inhibitor-induced apoptosis was further recognized with the finding that tumor necrosis factor (TNF)-␣ could inhibit the mitochondrial respiratory chain at the mitochondrial complex I site (14). However, contradictory reports showed that rotenone could inhibit apoptosis in other systems (17)(18)(19).…”
mentioning
confidence: 99%
“…Early reports showed that the complex I inhibitor rotenone and the complex b-c1 inhibitor antimycin could stimulate superoxide and hydrogen peroxide formation on submitochondrial particles (31,35). However, results of rotenone-induced mitochondrial ROS production measured at the cellular level appeared inconsistent with conflicting results reporting that rotenone could elevate cellular ROS production in some cases (11,36) while inhibiting cellular ROS production in others (17,37,38).…”
mentioning
confidence: 99%
“…One of the important functions of apoptosis is the elimination of preneoplastic and neoplastic cells [12]. In most forms of cell suicide, the signaling cascade utilizes reactive oxygen species as essential intermediate messenger molecules [13]. This is the reason that antioxidants are capable of inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 99%